Climate change will cause the spatial mismatch between sexually deceptive beetle daisy (Gorteria diffusa, Asteraceae) and its pollinator - Marta Kolanowska (Scientific Reports)
Abstract Climate change is a major driver of biodiversity loss, affecting complex ecological relationships. Plants that rely on animal pollen vectors for reproduction are more sensitive to habitat disturbance, as any change in local pollinator species composition, abundance or foraging behaviour can affect the reproductive success of a plant population. This study used ecological niche modelling to investigate the effects of global warming on the spatial overlap between the South African beetle daisy (Gorteria diffusa) and its sole pollen vector (Megapalpus capensis, beetledaisy fly). Gorteria diffusa is one of the few non-Orchidaceae species that can be pollinated by sexual deception. As predicted in this study, the general coverage of suitable niches of G. diffusa will not be significantly reduced in two of the climate change scenarios studied - SSP1-2.6 and SSP2-4.5. However, about 10% reduction of the potential range of the beetle daisy is expected to occur in SSP5-8.5. Based on the direction of range contraction, populations from the north-eastern part of the geographical range of the species seem to be most endangered due to the habitat loss. At the same time the geographical range of M. capensis will be significantly reduced in all climate change scenarios analysed. Even if global CO2 emissions reach net zero after 2050, the coverage of suitable niches of the insect will be over 20% smaller than currently estimated. Given the decline in pollinator availability due to the spatial mismatch between G. diffusa and the bee fly, the survival of north-western and south-eastern populations may be threatened as the insect will not be present in the areas suitable for beetle daisy occurrence. The maps produced in this study indicate areas that will be climatically suitable for the co-occurrence of beetle daisy and its pollinator in the future. These regions should be considered by local conservation authorities in developing more effective conservation strategies especially within South African Namaqualand.